REPRESENTASI BUDAYA JAWA DALAM FILM HATI SUHITA (Analisis Semiotika John Fiske dan Thomas Wiyasa Bratawijaya) - Kartika Bina Kaish; Bunga Surawijaya Ningsih; Muhammad Hidayatullah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The communication process cannot be separated from human life. Communication has a specific purpose. According to Berelson and Steiner, communication is a quality process. What is conveyed in the communication process can be informational messages, ideas, emotions, and so on. Meanwhile, what is conveyed by signs, signs can be images, words, numbers, and so on. One of the complex media in information symbols is film. The aim of this research is to find out, explain and analyze Javanese culture in the film Hati Suhita by Khilma Anis using the semiotic approach of John Fiske and Thomas Wiyasa Bratawijaya. This is a type of qualitative descriptive research which is analyzed using John Fiske's semiotic analysis and using the characteristics of Thomas Wiyasa Bratawijaya's Javanese culture to find a picture of Javanese culture in the film Hati Suhita. As a result, Javanese culture is defined as a culture that believes in God, respects each other, cares for each other, teaches us to be careful in speaking, advise, consider when making decisions and forgive each other. The television code that is often found and produces a picture of Javanese culture is the level of reality. Where at this level it helps researchers to see how the appearance, costumes, dialogue and behavior are presented in the film. When pointing the camera and lighting it is directed and visible clearly.